Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Di PT. Pharos Indonesia - Selaras Jagat, Muhammad Rakhan (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This research is motivated by the phenomenon of product sales instability during 2024 at PT. Pharos Indonesia, which indicates a decline and ongoing problems with employee performance. The objective of this study is to determine and empirically explain the effect of work motivation on employee performance, the effect of work discipline on employee performance, and the simultaneous effect of work motivation and work discipline on employee performance at PT. Pharos Indonesia. The methodology utilized in this study is a quantitative research approach. The population as the unit of analysis is the marketing department employees, with a total sample of 69 respondents selected using a saturated sampling technique. Primary data collection was conducted through direct observation, interviews, and the distribution of questionnaires to respondents. The data was processed using multiple linear regression analysis techniques. The results of the study prove that work motivation partially provides a positive contribution of 8,21% to employee performance. Work discipline partially provides a massive contribution of 20,06% to employee performance. The simultaneous test results obtained an F-count value of 36,326, which is greater than the F-table (3.13) with a significance level of <0.001. The coefficient of determination value indicates that both independent variables jointly contribute a 52,4% effect on employee performance, while the remaining 47,6% is influenced by various other factors not examined in this research. The conclusion of this study is that the variables of work motivation and work discipline, whether tested partially or simultaneously, are proven to have a positive and significant effect on improving employee performance at PT. Pharos Indonesia.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: Work Motivation; Work Discipline; Employee Performance